Organisational and grammatical features of explanations written by Biology undergraduates - Ting, Su Hie; Tee, Florence Pei Feng (2009)
The study examines the organisational and grammatical features of explanations written by Biology undergraduates at a tertiary institution. The explanation of a molecular biology technique was analysed in terms ofthe organisational structure of the text and two linguistic features relevant to explanations, namely, use ofpresent tense and sequence connectors. The 40 explanation texts selected for analysis were produced by two cohorts ofYear 3 undergraduates in a Biotechnology degree programme at a Malaysian tertiary institution: the cohort who learnt Science and Mathematics in Bahasa Melayu in Form 6; and the cohort who learnt these subjects in English. The results showed that about two-thirds of the verbs in the explanation texts were written in the present tense but there was inappropriate and perhaps inadvertent use of other tenses. It was also found that sequence connectors were not fully utilised to show the steps in the application of the molecular biology technique. Although all the texts analysed provided information about the technique, some did not show the organisational structure considered effective for explanations. The findings suggest that the explicit teaching of selected grammatical features significant to types of texts (e.g. explanation, argument) using whole texts as context would help students in producing better texts.